READING DIFFERENCES BETWEEN GREEK DYSLEXIC AND NON-DYSLEXIC UNIVERSITY STUDENTS IN GREECE - Rapti, Sofia; Pavlidis, George (The Modern Higher Education Review, 2020)
Until recently the vast majority of dyslexia research focused on English-speaking and children population, who tend to read significantly slower but mainly inaccurately, due to the inconsistency of the English language. This led to the wrong assumption that the main feature of dyslexia is inaccurate reading. However, results of research in phonologically consistent languages, such as Greek, Italian, German, Finnish, showed that reading speed is the main deficit of dyslexic readers in either children or adult population. The aim of this research was to investigate the differences in reading performance (reading speed, accuracy and comprehension) between Greek dyslexic university students and age-matched normal controls. A group of 26 Greek dyslexic university students was compared to a group of 28 non-dyslexics matched for age, sex and socio-educational level. All participants in the dyslexic group had a formal diagnosis of dyslexia. Results showed that dyslexics attained statistically significantly slower reading speed and made more reading errors compared to controls in all testing procedures (p<.001). However, dyslexics read at almost the same speed in both the aloud and silent reading conditions (p>.05) in contrast to non-dyslexics who read significantly faster in the silent condition (p<.05). Greek dyslexic university students were accurately differentiated from non-dyslexics based on the reading speed only (accuracy level 98.1%).